Between sport and bioethics grounding the philosophy of mountaineering - Eterović, Igor, povjesničar (2020)
Mountaineering encompasses a vast number of practices and it is becoming an umbrella term for a set of human outdoor practices. Although categorised as a sport, mountaineering resists to the standard definition of sport and especially to mainstream understanding of sport as a competitive activity. On the other hand, usual ethical questions concerning sports do not cover the vast majority of mountaineering practices, thus calling for a wider normative perspective – a bioethical analysis. It is argued that such an approach could ground the possibility of understanding mountaineering as a peculiar sort of sport, and differentiate its special features by using bioethical analysis. Thus, it is showed that mountaineering is a unique sport, but also that mountaineer shares and promotes a genuine life philosophy exemplifying a truly bioethical worldview. Mountaineer is guided by a unique set of core values encapsulated under something we can and should call the philosophy of mountaineering.
Planinarstvo obuhvaća velik broj aktivnosti, postajući krovni pojam za skup aktivnosti na otvorenom. Iako kategorizirano kao sport, planinarstvo se uvriježenoj definiciji sporta opire, a pogotovo glavnoj struji shvaćanja sporta kao natjecateljske aktivnosti. S druge strane, etička pitanja o sportu ne pokrivaju većinu planinarskih praksi, što za sobom povlači potrebu za širom normativnom perspektivom – bioetičkom analizom. Argumentira se da takav pristup može zasnovati mogućnost razumijevanja planinarstva kao posebne vrste sporta i razlučiti njegova posebna svojstva korištenjem bioetičke analize. Pokazuje se da je planinarstvo jedinstven sport, ali i da planinarstvo udjeljuje i promiče autentičnu filozofiju sporta, oprimjerujući odista bioetički pogled na svijet. Planinar je vođen jedinstvenim skupom sržnih vrijednosti sabranih pod nešto što bismo mogli i trebali zvati filozofijom planinarstva.
Bergsteigen umfasst eine Vielzahl von Praktiken und wird zum Oberbegriff für eine Reihe menschlicher Aktivitäten im Freien. Obwohl Bergsteigen als Sport eingestuft wird, widersetzt es sich der Standarddefinition des Sports und insbesondere der vorherrschenden Richtung im Verständnis des Sports als Wettkampfaktivität. Auf der anderen Seite decken die geläufigen ethischen Fragen in Bezug auf Sport nicht die überwiegende Mehrheit der Bergsteigerpraktiken ab, weshalb eine breitere normative Perspektive erforderlich ist – eine bioethische Analyse. Es wird argumentiert, dass ein solcher Ansatz die Möglichkeit begründen könnte, das Bergsteigen als eine besondere Sportart aufzufassen und seine besonderen Merkmale durch die Verwendung bioethischer Analyse zu differenzieren. Auf diese Weise wird gezeigt, dass Bergsteigen ein einzigartiger Sport ist, aber auch, dass Bergsteiger eine authentische Lebensphilosophie teilen und fördern, die eine fürwahr bioethische Weltanschauung exemplifiziert. Der Bergsteiger lässt sich von einer einzigartigen Reihe von Grundwerten leiten, die unter dem Begriff zusammengefasst sind, den wir Philosophie des Bergsteigens nennen können und sollen.
L’alpinisme comprend un grand nombre de pratiques et est ainsi devenu un terme générique pour un ensemble d’activités en plein air. Bien que l’alpinisme soit catégorisé comme un sport, il résiste à la définition classique de sport en tant que qu’activité de compétition. De plus, les questions habituelles d’éthique concernant le sport ne couvrent pas la grande majorité des pratiques de l’alpinisme, ce qui nous contraint à réfléchir à une perspective normative plus large – une analyse bioéthique. Nous affirmons qu’une telle approche peut permettre de comprendre l’alpinisme comme un genre de sport particulier et de différencier ses caractéristiques particulières en se servant d’une analyse bioéthique. Ainsi, en illustrant un regard sur le monde véritablement bioéthique, nous montrons que l’alpinisme est un sport unique, et que l’alpinisme partage et promeut une authentique vie philosophique. L’alpiniste est guidé par un ensemble unique de valeurs fondamentales rassemblées dans ce que l’on pourrait et ce que l’on devrait appeler une philosophie de l’alpinisme.
Bilješke uz tekst.
Bibliografske bilješke uz tekst ; bibliografija: str. 280-283.
Abstract ; Sažetak ; Zusammenfassung ; Résume.
Keywords: Planinarstvo -- Sport -- Bioetika -- Filozofska analiza -- Filozofija planinarstva